Correlation Analysis of Macro–Micro Parameters of Sandstone Based on PFC3D - Guohua Zhang; Qingqing Liu; Yubo Li; Zibo Li; Ke Jing; Tao Qin (Applied Sciences)
To address the issue of the low compression–tension ratio in the traditional parallel bond model (PBM), this study proposes an improved PBM incorporating a random distribution strategy of strong–weak contact groups. An L27(312) orthogonal experimental design was employed to construct 27 sets of numerical simulation schemes. Combined with Pearson correlation coefficient analysis and multivariate regression, the influence of twelve microscopic parameters on seven of the macroscopic mechanical properties of sandstone was systematically investigated, including elastic modulus (E), Poisson’s ratio (v), uniaxial compressive strength (σc), internal friction angle (φ), cohesion (c), crack damage stress ratio (σcd/σc), and compressive–tensile strength ratio (σc/σt). Based on these analyses, a quantitative relationship model between the macro and micro parameters was established and validated through numerical simulation and experimental comparison. The proposed method provides a theoretical foundation for the mechanical modeling of sandstone and the inversion of microscopic parameters.